Identification of Heat Spots and Thermal Insulation Deficiencies in Tropical Campus Buildings Using FLIR One - L. M. F. Purwanto; Sidi Ahyar Wiraguna (CV. Gio Architect, 2026)
Campus buildings in tropical regions are highly vulnerable to elevated surface temperatures due to intense solar radiation and the limited performance of existing thermal insulation systems. These conditions reduce indoor thermal comfort and increase cooling energy demand, particularly in spaces used for academic and administrative activities. The Henricus Constant Campus, as the selected case study, shows indications of uneven heat distribution within several key rooms. This study aims to identify heat spots and thermal insulation weaknesses in the tropical campus building using the FLIR One infrared thermography device. The method involved capturing thermal and visual images in three primary rooms: Lecture Room A.5.1, the Administration Office, and the Faculty Office. Measurements were conducted during midday, when heat intensity typically reaches its peak. Each thermal image was analyzed to observe temperature distribution patterns, detect thermal anomalies, and locate areas potentially experiencing insulation failure, particularly along wall–roof junctions, ceilings, and window openings. The results indicate that Lecture Room A.5.1 exhibits the highest concentration of heat spots, especially on the ceiling and around window areas exposed to direct sunlight. The Administration Office shows several anomalies along wall joints, while the Faculty Office demonstrates a relatively stable temperature distribution. These findings highlight the need for improved thermal insulation to enhance indoor comfort and energy efficiency in the campus building.